TWO STORIES - TWO DESTINIES - JABBAROVA, Maloxat (The journal of contemporary issues in business and government, 2021)
In the development of Uzbek literature, especially in the development of a new genre of realistic storytelling, the great poet Abdullah Kakhor played an important role in the development of Uzbek literature just as Hamza Hakim-zoda reformed dramaturgy and Cholpon Shepiyat, A. Kakhor also contributed to the development of storytelling, which is a small genre of the epic genre; each of his works is a work of art that fascinates the reader with its artistic beauty, the perseverance of its plot and compositional structure, and the perfection and sincerity of its language.